Multi-omics analyses demonstrate a critical role for EHMT1 methyltransferase in transcriptional repression during oogenesis - Demond, Hannah; Hanna, Courtney W.; Castillo-Fernandez, Juan; Santos, Fátima; Papachristou, Evangelia K.; Segonds-Pichon, Anne; Kishore, Kamal; Andrews, Simon; D'Santos, Clive S.; Kelsey, Gavin

(untitled) (Genome Research, 2023)
EHMT1 (also known as GLP) is a multifunctional protein, best known for its role as an H3K9me1 and H3K9me2 methyltransferase through its reportedly obligatory dimerization with EHMT2 (also known as G9A). Here, we investigated the role of EHMT1 in the oocyte in comparison to EHMT2 using oocyte-specific conditional knockout mouse models (Ehmt2 cKO, Ehmt1 cKO, Ehmt1/2 cDKO), with ablation from the early phase of oocyte growth. Loss of EHMT1 in Ehmt1 cKO and Ehmt1/2 cDKO oocytes recapitulated meiotic defects observed in the Ehmt2 cKO; however, there was a significant impairment in oocyte maturation and developmental competence in Ehmt1 cKO and Ehmt1/2 cDKO oocytes beyond that observed in the Ehmt2 cKO. Consequently, loss of EHMT1 in oogenesis results, upon fertilization, in mid-gestation embryonic lethality. To identify H3K9 methylation and other meaningful biological changes in each mutant to explore the molecular functions of EHMT1 and EHMT2, we performed immunofluorescence imaging, multi-omics sequencing, and mass spectrometry (MS)–based proteome analyses in cKO oocytes. Although H3K9me1 was depleted only upon loss of EHMT1, H3K9me2 was decreased, and H3K9me2-enriched domains were eliminated equally upon loss of EHMT1 or EHMT2. Furthermore, there were more significant changes in the transcriptome, DNA methylome, and proteome in Ehmt1/2 cDKO than Ehmt2 cKO oocytes, with transcriptional derepression leading to increased protein abundance and local changes in genic DNA methylation in Ehmt1/2 cDKO oocytes. Together, our findings suggest that EHMT1 contributes to local transcriptional repression in the oocyte, partially independent of EHMT2, and is critical for oogenesis and oocyte developmental competence.